A auditoria médica e o idoso em serviços de hemodinâmica e cardiologia intervencionista - Fernandes, Flávia Muniz Tessari (2011)
In Brazil, the medical audit has emerged as an activity aimed at ensuring the quality and efficiency of medical services coupled with the rational use of financial resources for service providers and operators of health plans. In this sense, the technical-scientific sectors of Medicine of high complexity, in particular the services of Hemodynamics and Interventional Cardiology, is needed for proper treatment of patients with appropriate cost-effectiveness. The increase in life expectancy, with the aging population and the representativeness of cardiovascular disease in the setting of morbidity and mortality in the country cause an increase in spending by operators of health plans with the elderly, since in them are concentrated and complex diseases highest accident. Thus, this paper aims to guide the actions of the medical auditor at the Department of Hemodynamics and Interventional Cardiology in relation to the elderly patient, considering the rapid and continuous evolution that presents cardiology in recent years, providing data on the operation of the Laboratory of Hemodynamics and the use of expensive materials, showing the indications and contraindications for the elderly population of the procedures performed, to be reasoned resolutions of medical audit in assessing the cases of responsibility, always in favor of best practice for the welfare of the patient, in light of new technologies